The role of the educational video in developing the visual intelligence of the students of the basic education stage from the point of view of their teachers (Journal of Hama University, 2022)
The current research aimed at developing the visual intelligence of basic education students from the point of view of their teachers in the schools affiliated to the Hama Education Directorate. It also aimed to test the average differences between teachers and teachers according to the variables: gender، and educational area.An educational tool and a questionnaire Teaching tools for teachers (18) male and female teachers from basic education in the Directorate of Education of the city of Hama during work in the second semester of the academic year 2021/2022 AD.The results of the research showed that the degree of approval by the teachers was high and it was also found that there was no statistically significant difference between the average scores of the sample members according to the variables of gender، experience and educational qualification.The research recommended the necessity of emphasizing the practice of teachers’ use of educational video because of its impact on the minds of students، and the introduction of educational video design programs within the curricula، in addition to holding training courses for teachers on the use of educational video design programs and providing them with the skills of using it.
Keywords: educational video، visual intelligence، basic education.